What matters to you? – Free-text comments in a questionnaire from patients undergoing radiotherapy. (March 2020) - Olausson, Kristina; Sharp, Lena; Fransson, Per; Nyholm, Tufve; Zackrisson, Björn; Östlund, Ulrika
Highlights: Involvement of patients during the radiotherapy process can improve patient satisfaction and make the patients feel safe. The experience and attitude of the staff and respect for the patient's autonomy are highly ranked values for patients undergoing radiotherapy. An implementation of person-centred care may help patients to become more involved in their care. Abstract: Background: Most cancer patients undergo external radiotherapy (RT) at some stage during their treatment trajectory and RT is often associated with unfamiliar procedures in a highly technical environment. The purpose of this study was to explore how patients experience RT and the related processes, as described in free-text comments in a large Swedish survey with questionnaires including items on psychosocial climate and treatment environment. Methods: The data consisted of free-text comments from one open-ended question: "Is there anything else you want us to know" and were analysed using qualitative content analysis. Results: Of 825 returned questionnaires, 261 contained free-text comments from patients (32%). The hand-written, free-text comments reflected the patients' experience of the RT process and were abstracted into the four major categories with sub-categories: experiencing the high-tech RT environment, understanding the RT procedures and side effects, dealing with daily life during RT, and the nurses' role and performance. The categories reflect the patients' experiences and emphasize how important it is to evaluate what really matters to the patients when changing procedures, practices, and how to minimize disturbances in the patients' daily lives. Conclusion: The main conclusions from this study are that the involvement of patients in choosing daily appointment times, providing good information during the RT process to make the patients feel safe, experience and attitude of the staff and respect for the patient's autonomy are highly ranked values for patients. An implementation of person-centred care may help relieve many of these problems.